TRIVIAL PURSUIT: I hælene på jæger-samlere - Veber, Hanne (Tidsskriftet Antropologi, 2001)
ERNEST S. BURCH, JR. & LINDA J. ELLANNA (eds.): Key Issues in Hunter-Gatherer Research. Oxford: Berg 1994. 534 sider. ISBN 0 85496 376 6. Pris: £19.95 (pb).